2018
DOI: 10.1111/ijau.12118
|View full text |Cite
|
Sign up to set email alerts
|

Audited financial reporting and voluntary disclosure: International evidence on management earnings forecasts

Abstract: In this paper, we extend prior research on the link between audited financial reporting and voluntary disclosure by examining international differences in the relationship between commitment to higher levels of audit verification of actual financial outcomes and management earnings forecasts (our proxy for voluntary disclosure), using firm‐level data from 30 non‐US countries. Our evidence that commitment to higher levels of audit verification (proxied by the choice of a Big 4 auditor, the amount of audit fees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
1
10
0
1
Order By: Relevance
“…In addition to the two input measures of country-level institutional development examined in Table 6 Panel A, we further follow T A B L E 6 Audit fee and management earnings forecasts disaggregation, and country-level institutional characteristics Liu et al (2018) and use an output measure of country-level institutional development, MarketDevelopment, in examining cross-sectional variation in the relationship between audit fees and disaggregated earnings forecast. This variable is constructed in a way that a higher index indicates better development in capital markets of a country.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the two input measures of country-level institutional development examined in Table 6 Panel A, we further follow T A B L E 6 Audit fee and management earnings forecasts disaggregation, and country-level institutional characteristics Liu et al (2018) and use an output measure of country-level institutional development, MarketDevelopment, in examining cross-sectional variation in the relationship between audit fees and disaggregated earnings forecast. This variable is constructed in a way that a higher index indicates better development in capital markets of a country.…”
Section: Resultsmentioning
confidence: 99%
“… In their study conducted in an international setting, Liu et al (2018) also document a positive relationship between audit fees and the incidence and frequency of earnings forecasts. However, unlike the incidence and frequency of earnings forecasts which more likely speak to the level of the firms' voluntary disclosures, earnings forecast disaggregation tends to have a stronger implication about the credibility of the firms' voluntary disclosures.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Rivera et al (2017) found that external assurance has a positive impact on the level of disclosure in integrated reports and that such assurance is necessary to ensure complete, correct and comparable information. Liu et al (2018) tested the relationship between audited information and disclosure. They observed that a higher level of auditing (the amount of fee is high) is positively associated with market response.…”
Section: Audit Quality and Integrated Reportingmentioning
confidence: 99%
“…Audit risk has been analysed mainly in the context of voluntary reporting, in which financial and non-financial reporting are conceived as complements; the truthfulness of auditable financial information reduces the risk that non-auditable forward-looking voluntary reporting will be unreliable (Athanasakou and Hussainey, 2014; Graham et al , 2005; Liu et al , 2018). The truthfulness of disclosure is becoming increasingly important in light of the international trend related to the integration of both financial and non-financial reporting in a single report (CSRD, 2021; ISSB, 2022).…”
Section: Introductionmentioning
confidence: 99%